Determination of Lead and Cadmium in Water by Flame Atomic Absorption Spectrometry - Xiaobin, Hu (Asian Journal of Chemistry, 2010)
A rapid coprecipitation technique was studied for the determination of trace lead and cadmium in water with flame atomic absorption spectrometry (FAAS) after preconcentration of lead and cadmium by using zinc diethyldithiocarbamate (DDTC) as coprecipitant and known amount of zinc(WZn0) as an internal standard. Since lead, cadmium and zinc were well-distributed in the homogeneous precipitate, the concentration ratio of lead to zinc or cadmium to zinc kept unchanged in any part of the precipitate. The concentration of lead (CPb1), cadmium (CCd1) and zinc (CZn1) in the final sample solution can be measured by FAAS. The rapid coprecipitation technique does not require complete collection of the precipitate. The amount of lead (WPb0) and cadmium (WCd0) in the original sample solution can be calculated from the following formula: WPb0 = (CPb1/CZn1) × WZn0; WCd0 = (CCd1/CZn1) × WZn0. The optimum pH range for quantitative coprecipitation of lead and cadmium is from 8-10. The 13 diverse ions tested gave no significant interferences in the lead and cadmium determination. Under optimized conditions, lead ranging from 0 to 40 μg and cadmium ranging from 0 to 8 μg were quantitatively coprecipitated with Zn-DDTC from 100 mL sample solution (pH 8.5). The rapid coprecipitation technique coupled with FAAS was applied to the determination of lead and cadmium in water sample with satisfactory results (recoveries in the range of 95-110 %, relative standard deviations < 6.0 %).